Russia's European agenda and the Baltic states - Šleivytė, J (Cranfield University, 2009)
Russia has always been a primary factor in the development of the Baltic States. It is impossible to analyse Baltic security without looking into the processes inside Russia and the prevailing trends vis-a-vis the Baltic States. However, the changes in the Baltic security landscape in the 21st century lack a comprehensive analysis. This thesis seeks to bridge the gap. Two key aims are being pursued in this thesis. The first is to present an analysis of Russia's European agenda under President Vladimir Putin and to examine the place of the Baltic States in this agenda. The second aim is to define Russia-related threats and challengers to the Baltic States, as well as prospects in Russo-Baltic relations. To attain these aims, inter-active approach to international relations, comprising three levels of analysis - the international system, the nation state (domestic level) and the individual (personality) level - has been applied. The neo-realist paradigm of international relations theory, comparative analysis and the Knudsen model, which addresses the peculiarities of relations between great powers and small states, are the methodological framework of the thesis. When analysing the development of Russo-Baltic relations in 1990-2006, this thesis focuses on the evolution of the Baltic States from factors to actors and their chance of shaping Russo-Baltic relations from within the enlarged EU and NATO. It also examines possibilities for more active engagement of Russia in the Baltic region. The thesis concludes with an analysis of perspectives for the Baltic States in countering Russia-related threats and building cooperativer elations with Russia. The author maintains that 'high politics' in Russo-Baltic relations has ended, yet, the tensions do remain in 'low politics'. Russia seeks to retain her political and economic influence in the Baltics by exploiting various tools, primarily economic levers and Baltic dependence upon Russian energy.